Investigation on the vibration balance approach for four-row star type reciprocating compressors. (August 2019) - Weifeng, Wu; Zhang, Zhao; Feng, Quanke
Abstract: Four-row star type reciprocating compressor was regarded as a compressor with low vibrations. However, an experiment of the new developed compressor shows serious vibration because of unbalanced force caused by the unique structural arrangement. In this paper, the investigation on the vibration balance approaches of four-row star type reciprocating compressor is carried out. The effects of cylinder arrangement, thermodynamic parameters and additional force on the vibration performance are investigated, which can effectively reduce the vibration and noise of the four-row star type reciprocating compressor and provide an optimization basis for the design of this type of compressor.